Scaling climate-adapted malt barley varieties in North Shewa, Ethiopia - Dejene Mamo Workie; Teklemariam Ayele Yiwegalet; Abiro Tigabie Mersha; Yehuala Kassa Meselu (Discover Agriculture)
Abstract Due to the development of new breweries and the expansion of existing malt factories, malt barley has become a highly demanded-commercial crop in Ethiopia. However, present efforts to increase malt barley productivity and supply have not been able to meet the domestic market’s needs. As a result, the scaling of climate-adapted malt barley varieties with its production package was done at North Shewa Amhara Ethiopia during the 2018 and 2019 main production seasons. In the first phase, HB1963, HB1964, Fanaka, and Ibon 174/03 were planted on seven farmers’ farms and evaluated by randomly selected 84 farmers using their selection criteria. The analysis of variance result showed that the highest yield was obtained from HB1963 (3.138 t/ha), followed by Ibon 174/03 (3.059 t/ha), HB1964 (2.324 t/ha) and Fanaka (2.123 t/ha). The cost–benefit analysis also revealed that the highest net benefit to total cost ratios was obtained from HB1963, followed by Ibon-174/03, HB1964, and Fanaka. In the second phase, the chosen varieties were scaled up in a clustered base on 12.3 hectares of land by participating 31 smallholder farmers during the main production season. Continuous field monitoring and evaluation were done by concerned experts and local farmers. The scale-up varieties, HB1963 and HB1964 gave 19.56% and 28.61% yield advantages over the local check respectively. The study's policy recommendations included expanding the use of high-yielding and well-adapted malt barley varieties, supporting both the formal and informal seed systems, and encouraging the malt barley producers and the domestic market to substitute imports.